Cleaning old cabinets: revealing the taxonomy of Sri Lankan wolf spiders (Araneae, Udubidae and Zoropsidae) - Polotow, Daniele; Griswold, Charles (Zootaxa, 2017)
The fauna of Udubidae and Zoropsidae of Sri Lanka is reviewed, the families are diagnosed and a distribution map is provided. The udubid genus Campostichomma Karsch, 1892 is diagnosed and redescribed, C. manicatum Karsch, 1892 is redescribed, and we propose three new species, based on females: C. harasbedda sp. nov., C. mudduk sp. nov. and C. alawala sp. nov. The zoropsid genus Devendra Lehtinen, 1967 is diagnosed and redescribed, D. seriatus (Simon, 1898), D. pumilus (Simon, 1898) and D. pardalis (Simon, 1898), are redescribed, and two new species are proposed: D. saama sp. nov. and D. amaiti sp. nov.